Transferability in the Automatic Off-Line Design of Robot Swarms: From Sim-to-Real to Embodiment and Design-Method Transfer Across Different Platforms - Kegeleirs, Miquel; Ramos, David Garzon; Hasselmann, Ken; Garattoni, Lorenzo; Francesca, Gianpiero; Birattari, Mauro (IEEE robotics and automation letters, 2024)
Automatic off-line design is an attractive approach to implementing robot swarms. In this approach, a designer specifies a mission to be accomplished by the swarm, and an optimization process generates suitable control software for the individual robots through computer-based simulations. Most relevant literature has focused on effectively transferring control software from simulation to physical robots. Here, we investigate 1) whether the design methods that generate control software are transferable across robot platforms and 2) whether control software generated via such methods is itself transferable. We experiment with two ground mobile platforms with equivalent functional capabilities. Our measure of transferability is based on the performance drop observed when control software and/or design methods are ported from one platform to another. Results indicate that, while the control software generated via automatic design is possibly transferable, better performance can be achieved when a transferable method is directly applied to the new platform.